High accuracy dual output voltage reference circuit for differential 10-bit successive approximation register analog to digital converter using 180nm technology - Yusuf, Siti Idzura (2020)
Voltage reference circuit produces reference voltage that is independent of fabrication process, temperature and supply voltage (PVT) variation. Differential successive approximation register (SAR) analog to digital converter (ADC) that converts an analog signal to digital signal is very much dependent on accurate reference voltage which defines the resolution of the converter. It requires two reference voltages namely VREF and VCM. VREF is used to set the full-scale voltage range while the common-mode voltage, VCM defines an initial value of most significant bit (MSB) digital output. VCM is designed as such that it is half of VREF and independent of process, voltage and temperature (PVT) variations. The deviation of the VCM develops an offset that shifts the transfer function of the ADC. Consequently, it reduces the dynamic range of the analog input to be digitised. The evolution of technology has favoured in a system on chip integration of the voltage reference and SAR ADC because it reduces design circuit area and consumes less power. However, based on the previous literatures, the impact of voltage reference circuits integrated with SAR ADC on a single die has not been discussed in depth. Hence, this thesis features the design and implementation of a high accuracy dynamic dual output voltage reference circuit for a 200kS/s differential 10-bit SAR ADC using a Silterra 0.18μm process with a supply voltage of 1.8V on a common die. The measurement of the fabricated chips is able to generate constant reference voltages for the VREF is that 1.2V±0.03V. Meanwhile, the VCM deviates as much as ±4mV between temperatures ranging from 0 C and 80 C across ±10% voltage supply variation. The measurement result shows that the circuit have sufficient drive capability to provide dual reference voltages to the SAR ADC. The voltage reference circuit achieves a good performance on the SAR ADC with 0.4LSB differential nonlinearity (DNL), 57.39dB Signal-to-noise and distortion ratio (SINAD) and an effective number of bits (ENOB) of 9.5 bits. The voltage reference circuit functions accurately in temperature sensor application between 0 C and 80 C temperature input range.